A Viral Satellite DNA Vector (TYLCCNV) for Functional Analysis of miRNAs and siRNAs in Plants. Issue 4 (22nd February 2017) - Ju, Zheng; Cao, Dongyan; Gao, Chao; Zuo, Jinhua; Zhai, Baiqiang; Li, Shan; Zhu, Hongliang; Fu, Daqi; Luo, Yunbo; Zhu, Benzhong
Abstract : A new small RNA overexpression system could highly overexpress not only artificial and endogenous miRNAs but also endogenous siRNAs in Nicotiana benthamiana. Abstract: With experimental and bioinformatical methods, numerous small RNAs, including microRNAs (miRNAs) and short interfering RNAs (siRNAs), have been found in plants, and they play vital roles in various biological regulation processes. However, most of these small RNAs remain to be functionally characterized. Until now, only several viral vectors were developed to overexpress miRNAs with limited application in plants. In this study, we report a new small RNA overexpression system via viral satellite DNA associated with Tomato yellow leaf curl China virus (TYLCCNV) vector, which could highly overexpress not only artificial and endogenous miRNAs but also endogenous siRNAs in Nicotiana benthamiana . First, we constructed basic TYLCCNV-amiRPDS(319L) vector with widely used AtMIR319a backbone, but the expected photobleaching phenotype was very weak. Second, through comparing the effect of backbones ( AtMIR319a, AtMIR390a, and SlMIR159 ) on specificity and significance of generating small RNAs, the AtMIR390a backbone was optimally selected to construct the small RNA overexpression system. Third, through sRNA-Seq and Degradome-Seq, the small RNAs from AtMIR390a backbone in TYLCCNV-amiRPDS(390) vector were confirmed to highly overexpress amiRPDS and specifically silence targeted PDS gene. Using this system, rapid functional analysis of endogenous miRNAs and siRNAs was carried out, including miR156 and athTAS3a 5′D8(+). Meanwhile, through designing corresponding artificial miRNAs, this system could also significantly silence targeted endogenous genes and show specific phenotypes, including PDS, Su, and PCNA . These results demonstrated that this small RNA overexpression system could contribute to investigating not only the function of endogenous small RNAs, but also the functional genes in plants.